EFFLUENT OF THE AFFLUENT: ANTHROPOLOGISTS' COMMENTS ON REMEDYING THE POLLUTION OF UMGUZA RIVER (IN ZIMBABWE - Thebe Phillip; Forzo Titang Franklin (Innovative Issues and Approaches in Social Sciences, 2020)
People’s activities of daily living continue to be central to environmental denigration. In Bulawayo, the second capital of Zimbabwe, big companies tend to deposit industrial waste in various streams that flow to the Umguza river located on the city’s margins. This has caused health and livelihood threats for the people living on the riverbanks. Unfortunately, the government’s remedial options have sometimes been reported to be ineffective− the reason why this river has remained subject to political and (largely scientific and quantitative) academic inquiry. This paper approaches the river from an anthropological perspective. It asks a variety of questions about management approaches and proffers a culture-centric lens towards the holistic understanding of the river. Debates on agency, ontology, perspectivism, the commodification of nature, and participation feature centrally. Despite inspiration from discussions with several people since 2012, the paper is not empirically grounded, and its content is a result of desktop and content analysis of literature, news, images, and videos related to pollution and the Anthropocene. The paper hopes to ignite and provoke further deliberations and empirical studies on the river.